Sunday

November 29, 2015
Posted by **Jennifer** on Wednesday, December 3, 2008 at 11:03am.

x^2 + 3x + 3 = 0

-1 +- sq.rt 1-4 (1)(3)

-1 +- sq.rt 1-12 =

-1 +- i sq.rt 11/2

Is this correct?

- Intermediate Algebra -
**Reiny**, Wednesday, December 3, 2008 at 11:57amno, I don't think you are using the quadratic formula correctly.

Do you have

for ax^2 + bx + c=0

x = (-b ±√(b^2 - 4ac)/(2a) ??

then for yours

x = (-3 ±√(9-4(1)(3))/2

= (-3 ±√-3)/2 which is a complex number

- Intermediate Algebra -
**Jennifer**, Wednesday, December 3, 2008 at 12:54pmyes i have that formula

i thought i was told to just put in the numbers for the variables

- Intermediate Algebra -